Optimization of a primary method for the determination of creatinine in human serum by GC-IDMS (INNOTEC, 2018)
Primary methods represent the highest hierarchical measurement level as they allow the implementation of traceability to the International System of Units. The aim of this work was the optimization of a primary method for the determination of creatinine in human serum by isotope dilution gas chromatography mass spectrometry (GC-IDMS) which is an adaptation of a reference method published in the Joint Committee for Traceability in Laboratory Medicine (JCTLM - BIPM) database. The isotopic equilibration and derivatization steps were optimized through a 23 experimental design and a one-way analysis of variance (ANOVA). The monitored output variables were the creatinine peak signal, the derivatization efficiency, the relative derivatization efficiency and bias. The optimized method shows higher efficiency and simplicity compared to the original method as well as a bias that remains fit for purpose. Once validated is intended to be used for the development of quality assurance tools for routine analysis of clinical laboratories.
Keywords: metrology; primary methods of measurement; IDMS; optimization